The Role of Common Ground on Object Use in Shaping the Function of Infants’ Social Gaze - Dimitrova, Nevena (Frontiers in Psychology, 2020)
Although infants’ social gaze has specific communicative functions, it remains unclear what they are. In this conceptual analysis paper, we provide a theoretical framework for the study of the functional aspects of eye gaze in early childhood. We argue that studying the communicative functions of infants’ eye gaze involves three premises: the centrality of the object, the importance of common ground on object use, and the role of parental interpretations. The ability to communicate intentionally begins when infants start referring to external objects. Beyond dyadic – infant–parent – emotional sharing, infant social gaze within the infant–parent–object triad becomes an increasingly complex communicative modality. As the predominant type of communicative referents in infancy, objects are thus central to early communication. Although they have affordances, objects are used in conventional ways shared between users (i.e., common ground). Parents transmit to infants the socio-cultural use of objects, which infants progressively learn and master. Accordingly, we argue that within early triadic interactions, the communicative function of infants’ eye gaze is shaped by the knowledge that the infant and the parent share on the socio-cultural use of the referent (i.e., the object). Importantly, before young children develop their ability to convey clear communicative functions, including with eye gaze, the interpretations and responses that parents provide to infants’ early communicative acts play a major role. Relying on these premises, we argue that when referring to objects for which the infant and the parent share common ground, the function of the infant’s social gaze becomes communicatively meaningful for the parent. The knowledge on the communicative referent (i.e., the object) shared between the infant and the parent thus shapes the course of communicative behavior, constitutes and reflects the interactive function of gaze, and cues parents into tailoring their communicative response according to the infant’s developmental needs. Through this theoretical framework for the study of the communicative function of infant eye gaze, an emphasis is put on the key role that socio-materiality plays in early communicative development.